Respuesta :
Answer:
(- 1, 1 )
Step-by-step explanation:
Given the 2 equations
y = 3x + 4 → (1)
y = x + 2 → (2)
Substitute y = 3x + 4 into (2)
3x + 4 = x + 2 ( subtract x from both sides )
2x + 4 = 2 ( subtract 4 from both sides )
2x = - 2 ( divide both sides by 2 )
x = - 1
Substitute x = - 1 into either of the 2 equations and evaluate for y
Substituting x = - 1 into (2)
y = - 1 + 2 = 1
Solution is (- 1, 1 )
Answer:
the solutions are
y = 1 ; x = -1
Step-by-step explanation:
Given two equations
3x + 4 = y....... (1)
x + 2 = y........ (2)
From equation (2), we make x subject of formula to form a new equation (3) by subtracting 2 from both sides of the equation
x + 2 - 2 = y - 2
x = y - 2...... (3)
Now we substitute the value of x in equation (3) into equation (1)
3x + 4 = y
3(y - 2) + 4 = y
3y - 6 + 4 = y
3y - 2 = y
Add 2 to both sides of the equation
3y - 2 + 2 = y + 2
3y = y + 2
Subtract your from both sides
3y - y = y + 2 - y
2y = 2
Divide both sides by 2
2y/2 = 2/2
y = 1
Now we substitute the new value of y = 1 into equation (2)
x + 2 = y
x + 2 = 1
x + 2 - 2 = 1 - 2
x = -1